THE INFLUENCE OF LEADERSHIP, WORK ENGAGEMENT AND RUBBER TAPPING PREMIUM ON WORK PERFORMANCE MEDIATED BY JOB SATISFACTION OF PT.PERKEBUNAN NUSANTARA III (PERSERO) KEBUN SARANG GITING EMPLOYEES - Gustiansyah Perdhana Putra; Yusniar Lubis; Syaifuddin (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
Employee work performance is influenced by many factors, one of which is employee satisfaction. Satisfaction is very important to improve work performance indirectly. Job satisfaction reflects a person's feelings towards his job. The aim of this research is to determine the influence of leadership, work engagement and tapping premiums on work performance mediated by employee job satisfaction at PT. Perkebunan Nusantara III Kebun Sarang Giting Employees. This type of research is quantitative descriptive, the research population is PT. Perkebunan Nusantara III rubber tappers (tappers) workers in Sarang Giting Gardens totaling 229 people, sampling using the Slovin formula with a total sample of 93 tappers. The results of this research show that there is an influence of leadership on the work performance of Kebun Sarang Giting Employees, there is no influence of work engagement on the work performance of Kebun Sarang Giting Employees employees, there is no influence of tapping premium on the work performance of Kebun Sarang Giting Employees employees, there is no influence of leadership on employee job satisfaction Kebun Sarang Giting Employees, there is an influence of work engagement on employee job satisfaction at Kebun Sarang Giting Employees, there is an influence of tapping premium on job satisfaction of Kebun Sarang Giting Employees employees, there is no influence of leadership on work performance which is mediated by employee job satisfaction at Kebun Sarang Giting Employees, there is an influence of work engagement on work performance is mediated by employee job satisfaction at Kebun Sarang Giting Employees, there is no influence of the tapping premium on work performance mediated by employee job satisfaction at Kebun Sarang Giting Employees, there is an influence of job satisfaction on employee work performance at Kebun Sarang Giting Employees.